Malignant Perivascular epithelioid cell tumour of the uterus without TFE3 gene rearrangement: a case report - Mu Xu; Jianhui Fu; Liangzhi Cai (BMC, 2024)
Abstract Background Perivascular epithelioid cell tumours (PEComas) are soft tissue tumours. These neoplasms belong to the family of mesenchymal tumours, which include angiomyolipomas, clear-cell sugar tumours of the lung, and PEComas not otherwise specified (NOS). The probability of a perivascular epithelioid cell tumour (PEComa) occurring in the uterus is low, and the incidence, diagnosis, treatment, and outcomes of such tumours are still unclear. Case presentation A 51-year-old woman presented a 4-year history of natural menopause. An intrauterine mass was detected via ultrasound examination; the mass showed a tendency to increase but caused no symptoms. The levels of tumour markers were within the normal range. Pathological analysis of the curettage revealed perivascular epithelioid differentiation of the endometrial tumour. Consequently, a laparoscopic total hysterectomy with bilateral adnexectomy was performed. No distant metastasis was detected via whole-body positron emission computed tomography (PETCT) after the operation. Fluorescence in situ hybridization (FISH) revealed no TFE3 gene rearrangement. Next-generation sequencing of bone and soft tissue revealed negative TSC1/2 and TP53 expression. No recurrence or metastasis was observed during the 18-month follow-up period. Conclusion PEComa of the gynecologic tract is a rare and challenging entity. Diffuse HMB-45 expression, TSC alterations and TFE3 rearrangement are characteristic of uterine PEComas. Surgical resection is the first choice. Genetic testing is helpful for determining the nature of the mass and for choosing targeted therapy. Further research is needed to establish treatment protocols.